Development of simple shoe dryer apparatus - Mohd Ridzwan, Adnan (2007)
This project is about Development of Simple Shoe Dryer Apparatus that can be used to helps people drying shoes in a short time. The objectives in this project are to create an easy method to dry a shoe in a short time and it can be used in many situations. Besides that, to design and fabricate an apparatus that can help in drying the shoes with simple action. This project involves the process of designing the simple shoe dryer by considering the functionality, shape, environment fitting, heating element, and the manufacturing cost for people to use it. The material of this design is easy to gain it, because it only using zinc sheet metal as raw material. So that the method joining that can be compatible in assembled this simple shoe dryer is rivet set processes. In assembled the wheel below the product, welding process is suitable because it will heat and melt the origin metal to joining. This project also required analysis to make sure the heating element for drying of the product to ensure the safety for the user indeed of publishing. After all the process had been done, this simple shoe dryer apparatus may help us to understand the fabrication and designing process that involved in this project.